Semantic Memory and Lexical Availability in Parkinson’s Disease: A Statistical Learning Study - Cardona, Juan F.; Grisales-Cardenas, Johan S.; Trujillo-Llano, Catalina; Diazgranados, Jesús A.; Urquina, Hugo F.; Cardona, Sebastián; Torres, Alejandra; Torres, Liliana A.; Gonzalez, Lina M.; Jaramillo, Tania; Cediel, Judith; Oñate-Cadena, Nelcy; et al. (Frontiers in Aging Neuroscience, 2021)
Parkinson's disease (PD) is a neurodegenerative disorder that causes a progressive impairment in motor and cognitive functions. In PD, deficits in semantic fluency (SF) have been described. However, the semantic categorization (SC) and lexical availability (LA) capacities have not been addressed in previous reports. The purpose of the present study was to characterize the cognitive performance of PD patients using a set of SC and SF tasks. Importantly, this study had the goal of determining which neuropsychological (lexical, semantic, or executive) variable could better classify participants as being PD or control with high accuracy. Thirty early PD patients and thirty controls were evaluated with neuropsychological screening and semantic memory (SM) tasks: picture naming, naming on oral description, word-picture matching. LA measures were obtained by having participants elicit words from ten semantic fields related to everyday life. Results showed that compared to healthy controls, PD patients' performance was not better in any three SM tasks. However, the PD group was significantly more impaired in the non-living category. Regarding LA, the number of words was inferior in PD patients, both larger and smaller semantic fields, showing a more inadequate recall strategy. Notably, the classification algorithms indicated that the SM task had high classification accuracy. In particular, the 'denomination of non-living things' had a classification accuracy of ~80%. These results suggest that basal ganglia deterioration in PD leads to search strategy deficits in SF and the potential disruption in semantic categorization. These findings are consistent with the embodied view of cognition.